Power tends to corrupt : Lord Acton's study of liberty - Lazarski, Christopher (NIU Press, 2012)
Lord Acton (1834-1902) is often called a historian of liberty. A great historian and political thinker, he had a rare talent to reach beneath the surface and reveal the hidden springs that move the world. While endeavoring to understand the components of a truly free society, Acton attempted to see how the principles of self-determination and freedom worked in practice, from antiquity to his own time. But though he penned hundreds of papers, essays, reviews, letters and ephemera, the ultimate book of his findings and views on the history of liberty remained unwritten. Reading a book a day for years he still could not keep pace with the output of his time, and finally, dejected, he gave up. Today, Acton is mainly known for a single maxim, power tends to corrupt, and absolute power corrupts absolutely. In Power Tends to Corrupt, Christopher Lazarski presents the first in-depth consideration of Acton's thought in more than fifty years. Lazarski brings Acton's work to light in accessible language, with a focus on his understanding of liberty and its development in Western history. A work akin to Acton's overall account of the history of liberty, with a secondary look at his political theory, this book is an outstanding exegesis of the theories and findings of one of the nineteenth century's keenest minds.